Studi Kebutuhan Jenis dan Kapasitas Fasilitas Tempat Pendaratan Ikan Kecamatan Bukit Batu Kabupaten Bengkalis Provinsi Riau - Zain, Jonny (Jurnal Perikanan dan Kelautan, 2016)
The research was conducted in Junli 2016. The aim of the research os to determine type and dimension/facilities and capacity suppose must be available on fish landing place in Subdistrict of Bukitbatu. The method of the research was survey. The data collected was fisherman activities data, type and dimension of vessels, kind and total provisions bought by the fisherman, and landed fish catching. The result showed that the type and dimension of facilities required by the fisherman are wharf 58 m in long, area of port basin 1661 m2, height of port basin 1,2 m, area of fish auction 15,4 m2, fuel oil tank capacity 1140 l, drinking water tank capacity 500 l, fresh water tank capacity 5815 l, freezer capacity 2,3 ton, management room area 6 m2, store area 6 m2, provision stall 6 m2, canteen 6 m2, praying room 6 m2, toilet 3 m2, parking area 144 m2. To build these facilities, it is need land area about 209,4 m2.